Orientational binding modes of reporters in a viral-nanoparticle lateral flow assay. Issue 1 (30th September 2016) - Kim, Jinsu; Poling-Skutvik, Ryan; Trabuco, João R. C.; Kourentzi, Katerina; Willson, Richard C.; Conrad, Jacinta C.
Abstract : Capture of ellipsoidal viral-nanoparticle reporters in a model lateral flow assay is enhanced by behavior of the anisotropic reporters in the local flow field. Abstract : Using microscopy and image analysis, we characterize binding of filamentous viral nanoparticles to a fibrous affinity matrix as models for reporter capture in a lateral flow assay (LFA). M13 bacteriophage (M13) displaying an in vivo -biotinylated peptide (AviTag) genetically fused to the M13 tail protein p3 are functionalized with fluorescent labels. We functionalize glass fiber LFA membranes with antibodies to M13, which primarily capture M13 on the major p8 coat proteins, or with avidin, which captures M13 at the biotin-functionalized tail, and compare orientational modes of reporter capture for the side- versus tip-binding recognition interactions. The number of captured M13 is greater for side-binding than for tip-binding, as expected from the number of recognition groups. Whereas two-thirds of side-bound M13 captured by an anti-M13 antibody bind immediately after colliding with the membrane, tip-bound M13 prominently exhibit three additional orientational modes that require M13 to reorient to enable binding. These results are consistent with the idea that the elongated M13 shape couples with the complex flow field in an open and disordered fibrous LFA membrane to enhance capture.